Coping strategies to predict the psychological well-being of college students during the COVID-19 pandemic - Karina Angelica; Monique Elizabeth Sukamto; Clara Citra Chandra; Kelvin Andrea (Humanitas: Indonesian Psychological Journal, 2022)
The COVID-19 pandemic in Indonesia has forced college students to undergo online learning. Various problems that arise due to this pandemic, especially those related to academic achievement, can disrupt the students' psychological well-being. This study investigated coping strategies' role in predicting college students' psychological well-being during the pandemic's first wave. Two hundred eleven students participated online in this quantitative study and completed the shortened version of the Psychological Well-Being Scale and the Brief Cope Inventory. The regression analysis results show that problem-focused coping strategies, such as planning and the use of instrumental support, significantly predict the increase in female students' psychological well-being. In contrast, only active coping positively predicts psychological well-being in male students. Dysfunctional coping strategies, such as behavioral disengagement and denial, significantly predict the decline in female students' psychological well-being. On the other hand, venting showed a significant role in predicting the increased psychological well-being of female students. Emotion-focused coping strategies do not significantly predict psychological well-being in female and male students. Therefore, regarding the psychological well-being of college students during the first wave of the COVID-19 pandemic, coping strategies, especially problem-focused and dysfunctional strategies, contribute differently to female and male students.